2016
DOI: 10.1073/pnas.1608247113
|View full text |Cite
|
Sign up to set email alerts
|

Probe for the measurement of cell surface pH in vivo and ex vivo

Abstract: We have developed a way to measure cell surface pH by positioning a pH-sensitive fluorescent dye, seminaphtharhodafluor (SNARF), conjugated to the pH low insertion peptide (pHLIP). It has been observed that many diseased tissues are acidic and that tumors are especially so. A combination of effects acidifies tumor cell interiors, and cells pump out lactic acid and protons to maintain intracellular pH, acidifying the extracellular space. Overexpression of carbonic anhydrases on cell surfaces further contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(162 citation statements)
references
References 48 publications
7
153
0
Order By: Relevance
“…Despite 326 studies demonstrating the efficacious, monotherapeutic use of 5FC in murine models of 327 aspergillosis, this drug is typically not applied in clinical settings (9, 40). To our 328 knowledge, no data is available to indicate the pH in the lung during aspergillus infection 329 however from studies of other pathological states it has been shown that cellular 330 damage, inflammation and infection can lead to a localised reduction of pH below pH 7 331 (41)(42)(43). This coupled with the ability of Aspergillus sp.…”
mentioning
confidence: 99%
“…Despite 326 studies demonstrating the efficacious, monotherapeutic use of 5FC in murine models of 327 aspergillosis, this drug is typically not applied in clinical settings (9, 40). To our 328 knowledge, no data is available to indicate the pH in the lung during aspergillus infection 329 however from studies of other pathological states it has been shown that cellular 330 damage, inflammation and infection can lead to a localised reduction of pH below pH 7 331 (41)(42)(43). This coupled with the ability of Aspergillus sp.…”
mentioning
confidence: 99%
“…Recent studies using a fluorophore with a pH-dependent emission spectrum have shown that the pH in the vicinity of the plasma membrane of cancer cells is about 0.3–0.7 pH units lower than the bulk extracellular pH [12]. In experiments in vitro, where the pH of the solution in which the cancer cells are growing (bulk pH) is maintained at pH 7.4, the cell surface pH for highly metastatic cells has been shown to be around pH 6.7.…”
Section: Extracellular Aciditymentioning
confidence: 99%
“…The conjugation of the pH-sensing fluorescent dye SNARF to a pHLIP results in a compound that can measure pH at the surface of individual cells, which differs greatly from the more easily and commonly measured bulk pH [12]. Currently, approaches for cell surface pH mapping using SNARF-pHLIP in liquid and solid biopsy samples are being developed, which might result in an opportunity to get information about the metabolic status of tumors, ultimately aiding in the prediction of tumor aggressiveness and the tailoring of therapy.…”
Section: Applications Of Phlip Technologymentioning
confidence: 99%
“…We choose to treat cells with constructs at pH7.8, which is slightly above than normal physiological pH7.4, since it was shown that pH at the surface of cancer cells, especially highly metastatic cancer cells such as 4T1, is lower even when pH of media is normal (Anderson et al, 2016). We also choose to treat cells with constructs at pH5.5, which is slightly lower than mean pH established at the surface of cancer cells within tumors, pH6.0, (Anderson et al, 2016) with main goal to enhance difference in cellular uptake of niosomes in this model experiment. The fluorescent signal from the cells treated with niosomes was analyzed using cellometer (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Family of pH (Low) Insertion Peptides (pHLIP ® peptides) are under development as novel agents, which target tumor acidity (Andreev et al, 2009, Weerakkody et al, 2013). The peptides sense pH at the surface of cancer cells, where it is the lowest (Anderson et al, 2016), and insert into cellular membranes (Reshetnyak et al, 2006, Reshetnyak et al, 2007, Reshetnyak et al, 2008, Andreev et al, 2010). Nanocarriers decorated with pHLIPs are biocompatible, can target tumor and demonstrate enhanced cellular uptake by cancer cells (Du et al, 2014, Wijesinghe et al, 2013, Yao et al, 2013b, Arachchige et al, 2015, Yao et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%